Implied object direction from eye location enhances animacy ratings but not detection of chasing behavior - Takahiro Kawabe (Scientific Reports)
Abstract Understanding how humans perceive animacy in dynamic visual stimuli is fundamental to elucidating the mechanisms underlying visual social cognition. While both object geometry and eye-like features are known to independently influence animacy impressions, their interactive effects remain insufficiently explored. This study investigates how the combination of object geometry and the location of eye-like patterns modulates the perception of animacy in non-living moving objects. In Experiment 1, we manipulated the pointing direction of triangular objects and the location of eye-like features (near the vertex, near the edge, or absent), and found that animacy impressions were enhanced when the direction of motion aligned with the gaze-implied object direction, irrespective of the object’s geometrical shape. Experiment 2 examined whether this effect generalizes to an objective task, in which participants identify a target triangle chasing a green disk among distractors. Although the gaze-implied object direction did not significantly influence detection sensitivity, the spatial location of the eye pattern within the triangular shape continued to weakly modulate participants’ performance. These findings suggest that cues related to eye location contribute to subjective animacy at multiple stages of cognitive processing, with their impact varying depending on task demands and perceptual context.